Analysis of South America coins of the XIX and XX centuries by XRF technique - Raysa Costa Nardes (Brazilian Journal of Radiation Sciences, 2021)
In this work, the elemental composition of 21 coins from nineteenth and twenty centuries of South America belonging to a private collection were performed using the X-Ray Fluorescence (XRF). Different coin numismatic catalogs were used as reference material. The XRF measurements were performed using ARTAX 200 system (Bruker AXS Inc., Madison, WI, USA), which consists of an X-ray tube with Mo anode and a Silicon Drift Detector. The analyses were performed with a voltage and current of 40 kV and 600 μA, respectively, and an acquisition time of 100 s. It was possible to evaluate that all twenty-one pieces were made from metallic alloys. The major elements found were Fe, Cu, Ni, Zn and Sn. Twenty coins were consistent with their cataloged version, on the other hand, only one coin showed a different chemical composition from its cataloged version. So, this result can be an indication that this coin may be a fake.